Driving Engagement: How Information Quality and Event Marketing Shape Toll Road Companies' Image on Instagram - Salfhaoctha Friemay Aliefia Poetry; Leila Mona Ganiem; Irmulansati Tomohardjo (PT. Anagata Sembagi Education, 2025)
PT Jasa Marga, as a company in the field of transportation services and toll road management infrastructure in Indonesia, faces the challenge of understanding and utilizing the potential of social media to build a positive corporate image. Pre-surveys to followers indicate a fairly good understanding of the company's basic information, but need improvement in certain information such as rest areas, toll rate discounts, and